A general overview and bibliometric analysis of seven ACM hypertext and web conferences. (2017) - Agarwal, Swati; Mittal, Nitish; Sureka, Ashish
Bibliometric analysis of published scientific papers is a widely used practice to conduct quantitative evaluations and assessments of conferences. In this study, we performed an in-depth bibliometric, scientometric and exploratory analysis of ACM SIGWEB sponsored conferences by visually analysing the DBLP database. We conducted a series of experiments and empirical analysis to answer several questions. Our results showed that the articles published in SIGWEB conferences stem from a variety of countries while the degree of cross-country collaboration is relatively low and that most co-authors of publications are by researchers who all reside in the same country. Collectively, SIGWEB conferences have a higher hosting rate and local community participation in places where the USA and Europe make the greatest conference contributions. Our results showed that the participation of female authors in SIGWEB conferences is increasing while in contrast, there is a huge gender imbalance in leadership and official conference positions.